Perception of Local Communities Towards the Conservation Terubok - Amin Mahir, Abdullah; Dayang Affizzah, Awang Marikan; Nur Athirah, Binti Bakeri (Macrothink Institute, Inc., 2019)
Terubok is one of the famous, important commercially fish in Malaysia and has high economic value which only can be found in Sarawak rivers. However, this species has been threatened in the past 15 years due to heavy exploitation. Hence, this study was done to examine the perceptions of local in conserving and sustaining the terubok population. An attitudinal study is increasingly being adopted as tools for evaluating public understanding, acceptance and the impact of conservation interventions. This study examines the perception and views of local community towards the dynamic resources, government intervention, unique features and livelihood sustainability which acts as a basis on conserving terubok. The findings of these studies show that almost all of the respondents show a highly positive attitude towards conserving terubok. Local community are really well aware with the importance of terubok. Hence, this study has proof that the local community has a positive attitude towards conserving terubok.